Efektivitas Segmentation, Targeting, And Positoning Terhadap Perilaku Konsumen (Study Kasus Pada Akun Instagram @hayu_outfit) - Nina Lelawati; Yateno; Amar Asyam Alfaras (Universitas Muhammadiyah Metro, 2024)
The effectiveness of segmentation, targeting, and positioning on consumer behavior carriedout by the @hayu_outfit Instagram account. The purpose of this study is to examine the effectof the effectiveness of segmentation, targeting, and positioning on consumer behavior carriedout by the @hayu_outfit Instagram account. This type of research includes correlativequantitative research. The population in this study were 94buyers taken from regular buyersat @hayu_outfit. The method used in the study is the type of data to be used, namely primarydata. Of the 117 questionnaires distributed, only 94 questionnaires could be processed. Thedata is then tested for data quality by using the validity test, reliability test. After testing thequality of the data then tested using the Spearman rank test. Then the data were analyzedusing the coefficient of determination test. The results of this study are the effect of theeffectiveness of segmentation, targeting, and positioning on consumer behavior carried outby the @hayu_outfit Instagram account. The effectiveness of segmentation has a positive andsignificant effect on consumer behavior, targeting has a positive and significant effect onconsumer behavior, positioning has a positive and significant effect on consumer behavior.